A Cross-Country Empirical Study Towards the Impact of Following ISO Management System Standards on Euro-Area Economic Confidence - Ştefan Daniel Armeanu; Georgeta Vintilă; Ştefan Cristian Gherghina (Amfiteatru Economic Journal, 2017)
This study aims to examine the impact of following ISO management system standards on economic sentiment indicator (ESI) as proxy of economic agents' general view concerning economic activity, for 21 European Union member states over 2005-2014. The empirical research comprises ISO standards with reference to management systems towards quality (ISO 9001, ISO 13485, ISO 16949), food safety (ISO 22000), environment (ISO 14001), and information security (ISO 27001). Panel data fixed effects regression models provide support for a positive impact of the quality management systems related to automotive industry, as well as information security management systems, on the ESI. Further, dynamic panel data approach by way of two-step system generalized method of moments emphasizes a positive influence of quality management systems standard for the medical device industry on Euro-area economic confidence, but a negative effect of food safety management systems. Also, ISO 9001, ISO 22000, and ISO 14001 Granger cause ESI.
Keywords: C33; L15; 330; ISO management systems standards; EU economic sentiment indicator; panel data fixed effects regression model; generalized method of moments; Granger causality